KEDUDUKAN OBJEK JAMINAN KEBENDAAN DENGAN KEPEMILIKANATAS NAMA PIHAK KETIGA DALAM PROSES KEPAILITAN: Studi Putusan Nomor 08/Pdt.Sus-GLL/2019/PN.Niaga.Jkt.Pst - Utami, Septia Salikhah (Journal Social Sciences and Humanioran Review, 2024)
The provision of material guarantees by third party can lead to struggles betweencurators and creditors in carrying out the execution of collateral objects inthebankruptcy, as is the case with Decision Number 08/Pdt.Sus- GLL/2019/PN.Niaga.Jkt.Pst. This research brings several formulations of theproblem, namely how is the position of the object of material guarantees on behalf ofthird party and how is the ratio decidendi analysis of the panel of judges in DecisionNumber 08/Pdt.Sus-GLL/2019/PN.Niaga.Jkt.Pst which includes objects of materialguarantees for names of third party into bankruptcy assets. This research is anormative juridical research with statutory and case approaches. The data obtainedcomes from secondary data and tertiary data in the form of interviews collectedbyliterature study to be analyzed descriptively qualitatively. The results of the studyshow that referring to Article 1 point 1 in conjunction with Article 21 of theBankruptcy Law, the position of the collateral object with ownership on behalf of athird party does not include bankrupt assets even though material guarantees havebeen charged to these assets so that the ratio decidendi of the panel of judges indeciding lawsuit No. 08/Pdt.Sus-GLL/2019/PN.Niaga.Jkt.Pst has been mistaken.